2021
DOI: 10.1016/j.esmoop.2021.100231
|View full text |Cite
|
Sign up to set email alerts
|

Drug-drug interactions between palbociclib and proton pump inhibitors may significantly affect clinical outcome of metastatic breast cancer patients

Abstract: Background: Proton-pump-inhibitors (PPIs) are frequently prescribed for the management of anticancer drug-related gastrointestinal symptoms. Palbociclib is a weak base with pH-dependent solubility and potential drug-drug interaction at the absorption level may affect clinical pharmacokinetics. The current study was aimed at investigating the effect of co-administration of PPIs and palbociclib on progression-free survival (PFS) in metastatic breast cancer (mBC) patients. Patients and methods: Patients affected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 34 publications
4
29
0
1
Order By: Relevance
“…Gastric pH changes by proton pump inhibitors (PPIs) may alter the oral bioavailability of targeted agents that exhibit pH-dependent solubility [ 3 , 4 ]; however, the clinical impact of such interaction remains a controversial topic that is currently debated [ 12 ]. In line with findings showing that co-administration of rabeprazole reduced palbociclib bioavailability [ 13 ], we recently demonstrated that concomitant PPIs substantially decreased progression-free survival (PFS) in metastatic breast cancer patients treated with palbociclib [ 13 ].…”
Section: Introductionsupporting
confidence: 64%
“…Gastric pH changes by proton pump inhibitors (PPIs) may alter the oral bioavailability of targeted agents that exhibit pH-dependent solubility [ 3 , 4 ]; however, the clinical impact of such interaction remains a controversial topic that is currently debated [ 12 ]. In line with findings showing that co-administration of rabeprazole reduced palbociclib bioavailability [ 13 ], we recently demonstrated that concomitant PPIs substantially decreased progression-free survival (PFS) in metastatic breast cancer patients treated with palbociclib [ 13 ].…”
Section: Introductionsupporting
confidence: 64%
“…In the study by Re et al, PFS was 14 months versus 37.9 months in patients who received and did not receive concominant PPIs with palbociclib, respectively. Additionally, no other significant variable affecting PFS was detected in the multivariate analysis [ 28 ]. In the results we presented, PFS was similar to that in this trial in patients who received PPIs, but PFS could not be reached yet in patients who did not receive PPIs.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of these co-treatments in terms of survival will be evaluated later, especially because the correlation between palbociclib plasma concentration and hematologic toxicity can lead to dose reductions. Recent studies suggest a link between co-medication (statin use) and neutropenia occurrence (n = 78), and a negative influence of antacids on the survival of patients treated with palbociclib (p < 0.0001) [22,26]. It would be relevant to analyze the various PK/PD correlations and specifically the modulation of palbociclib concentration on treatment efficacy in our cohort.…”
Section: Discussionmentioning
confidence: 97%